Effectiveness of Law in the Policy of Restricting the Operation of Goods Vehicles - Annie Myranika; Dian Yulviani; Siti Humulhaer; Dwi Nur Afrianto (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2025)
Indonesia, as a country governed by the rule of law, places law as the primary instrument for ensuring certainty, justice, and benefit. In this context, Tangerang Regent Regulation No. 12 of 2022 was enacted as a strategic policy to reduce the rate of traffic accidents involving goods vehicles, especially dump trucks and heavy vehicles. However, its implementation faces various challenges. Therefore, this study aims to analyze the effectiveness of this regulation from both normative and empirical perspectives. This study uses an empirical legal method with a descriptive analytical approach. The research data were obtained through observation and interviews with the Transportation Agency officials and the Tigaraksa community. The results show that although the substance of the regulation is appropriate, its effectiveness is still hampered by limited personnel, monitoring facilities, and low legal awareness among truck drivers. However, there are supporting factors in the form of inter-agency coordination, community participation, and a decrease in violations at several vulnerable points. Overall, this study shows that the regulations have provided a relevant regulatory framework to reduce public transportation accidents, but their practical impact is still hampered by limitations in enforcement and infrastructure, thus requiring the strengthening of monitoring mechanisms and increasing drivers’ legal awareness. [Indonesia sebagai negara hukum menempatkan hukum sebagai instrumen utama dalam menjamin kepastian, keadilan, dan kemanfaatan. Dalam konteks tersebut, Peraturan Bupati Tangerang Nomor 12 Tahun 2022 ditetapkan sebagai kebijakan strategis untuk menekan tingkat kecelakaan lalu lintas yang melibatkan mobil barang, terutama truk tanah dan kendaraan berat lainnya. Meskipun demikian, implementasinya masih menghadapi berbagai permasalahan. Oleh karena itu, penelitian ini bertujuan untuk menganalisis efektivitas regulasi tersebut dari aspek normatif maupun empiris. Penelitian ini menggunakan metode hukum empiris dengan pendekatan deskriptif-analitis. Data penelitian diperoleh melalui observasi dan wawancara dengan aparat Dinas Perhubungan serta masyarakat Tigaraksa. Hasil penelitian menunjukkan bahwa meskipun substansi peraturan telah sesuai kebutuhan, efektivitas penerapan masih terkendala oleh keterbatasan personel, sarana pengawasan, serta rendahnya kesadaran hukum pengemudi. Namun demikian, terdapat faktor pendukung berupa koordinasi antarinstansi, partisipasi masyarakat, serta adanya penurunan pelanggaran di sejumlah titik rawan. Secara keseluruhan, penelitian ini menunjukkan bahwa regulasi telah menyediakan kerangka regulasi yang relevan untuk menurunkan kecelakaan kendaraan angkutan, namun dampak praktisnya masih terhambat oleh keterbatasan penegakan dan infrastruktur, sehingga diperlukan penguatan mekanisme pengawasan serta peningkatan kesadaran hukum para pengemudi].